Fluorescence assay to predict activity of the glycopeptide antibiotics - Vimberg, Vladimir; Gazak, Radek; Szűcs, Zsolt; Borbás, Aniko; Herczegh, Pal; Cavanagh, Jorunn Pauline; Zieglerova, Leona; Závora, Jan; Adámková, Václava; Balikova Novotna, Gabriela (The Journal of antibiotics, 2019)
Here, we describe a fluorescent assay developed to study competitive binding of the glycopeptide antibiotics to live bacteria cells. This assay demonstrated that the mechanism of action of the lipoglycopeptide antibiotics strongly depends on the hydrophobicity of the substitutes, with the best antibacterial activity of the glycopeptide antibiotics equally sharing properties of binding to D-Ala-D-Ala residues of the nascent peptidoglycan and to the membrane.
Keywords: peptidoglykan; buněčná stěna; Vancomycin-Resistant Enterococci; Staphylococcus aureus; rhodaminy; antibakteriální látky; barvení a značení; Vancomycin; Staining and Labeling; Microbial Sensitivity Tests; Teicoplanin; Rhodamines; Fluorescence; mikrobiální testy citlivosti; glykopeptidy; Cell Wall; enterokoky rezistentní vůči vankomycinu; Peptidoglycan; fluorescence; Protein Binding; Enterococcus faecium; Lipoglycopeptides; vankomycin; lipoglykopeptidy; Glycopeptides; Anti-Bacterial Agents; teikoplanin; vazba proteinů